Mom feels what her child feels: thermal signatures of vicarious autonomic response while watching children in a stressful situation - Manini, Barbara; Cardone, Daniela; Ebisch, Sjoerd; Bafunno, Daniela; Aureli, Tiziana; Merla, Arcangelo (Frontiers in Human Neuroscience, 2013)
Maternal attunement with an infant's emotional states is thought to represent a distinctive feature of the human primary bond. It implies the mother’s ability of empathizing with her child in order to fulfil the child’s needs in an immediate and appropriate manner. Thus, it is particularly involved in stressful situations. By assuming that maternal attunement embodies a direct sharing of physiological responses with the child, we compared the autonomic response of mothers observing their own distressed child with those of other women observing an unknown child involved in an ecological distressful condition (mishap paradigm). The hypothesis was that the adult’s response was more attuned with the child’s response in the former group than in the latter group. The autonomic response was non-invasively evaluated through the recording of the thermal facial imprints by means of thermal infrared (IR) imaging. Nine mother-child dyads and nine woman-unknown child dyads were studied. We found marked similarities between the facial temperature dynamics of women and children along the experimental procedure, thus providing evidence for a direct emotional sharing within the adult-child dyad. The evidence for common dynamics in the time course of the temperatures was assessed through correlation analysis and, nevertheless, resulted stronger in the mother-child dyads than in the other women–child dyads. In addition, temporal analysis showed a faster response in mothers than in other women, thus confirming our study hypothesis. Besides confirming the extraordinary capability of thermal infrared imaging to preserve ecological context in the study of social or non-verbal interactions, these results suggest that maternity appears to potentiate the emotional attunement with the child. Although based on preliminary results, this study opens new perspectives in the study of the factors modulating vicarious socio-emotional processes.